DO FINANCIAL AND DIGITAL LITERACY MATTER? EVIDENCE FROM SMES OWNED BY PERSONS WITH DISABILITIES IN CENTRAL JAVA AND EAST JAVA - Umiko Bunga Indriyani; Erna Fitri Komariyah; Popi Andiyansari; Ifah Rofiqoh (Berkala Akuntansi dan Keuangan Indonesia, 2026)
Disability-owned SMEs play an essential role in promoting inclusive economic growth; however, their business performance remains relatively low compared to conventional SMEs. This condition is frequently linked to limited financial and digital literacy, both of which are crucial in an increasingly digital business landscape. The purpose of this research is to investigate whether financial and digital literacy notably impact the performance of SMEs owned by individuals with disabilities. Employing a quantitative methodology, data were gathered through a structured survey of disability-owned SMEs and analyzed using partial least squares structural equation modeling (PLS-SEM). Findings reveal that both financial and digital literacy positively and significantly influence SME performance. Financial literacy enhances business performance by improving financial management and decision-making. In contrast, digital literacy strengthens performance by enhancing the use of digital tools, expanding market access, and improving operational efficiency. The findings confirm that literacy-based human capital is a critical determinant of business performance within the context of inclusive entrepreneurship. This study concludes that strengthening financial and digital literacy is essential to improving the sustainability and competitiveness of disability-owned SMEs. The results offer practical implications for policymakers and development agencies in designing targeted, inclusive capacity-building programs to support entrepreneurs with disabilities.